Spiritual Revolution Based on Transformative Islamic Education: Reconstruction of Religious Values From Upstream to Downstream in an Era of Disruption - Neng Wina Shalehah (STAI Al-Mas'udiyah, 2025)
This article aims to explore the concept of spiritual revolution through transformative Islamic education, and to examine how religious values can be holistically reconstructed to address the challenges of changing times. With this goal, the research aims to provide insights into the importance of innovation in Islamic education to create a comprehensive spiritual transformation. The research method employed is a qualitative approach, consisting of literature review and conceptual analysis. The literature review was conducted to identify contemporary perspectives on the spiritual revolution in Islamic education, while conceptual analysis was used to understand the principles of transformative Islamic education that can be applied in the current context. The research findings indicate that a spiritual revolution can be achieved through reforms in the Islamic education system, focusing on character formation, integration of knowledge, and strengthening spirituality. The implementation of transformative Islamic education, which emphasizes a balance between intellectual and spiritual development, can produce a generation that is not only adaptive to the changing times but also capable of maintaining their identity and religious values as their life foundation. The implication of this research is that transformative Islamic education needs to be optimized to produce individuals with high adaptive capabilities in facing the challenges of change, while still adhering to the spiritual values that form the foundation of their lives.